Dampak Pinjol Pada Generasi Z Dan Generasi Milenial - Uyun, Linatul; Herwiyanti, Eliada; Budiarti, Laeli (Sosio e-Kons, 2024)
The purpose of this study was to determine the impact of online lending (pinjol) on generation Z and the millennial generation. This type of research is qualitative with a phenomenological approach, sample collection using random sampling and snowball sampling techniques. There are 26 informants consisting of 13 women and 13 men, generation Z is the most informants with 17 informants. The results showed that the lack of understanding of financial literacy in generation Z and the millennial generation, this has an impact on the misuse and financial difficulties experienced by generation Z and the millennial generation. The lack of financial literacy and knowledge about legal and illegal pinjol applications has resulted in generation Z and millennials being trapped in terror and illegal data dissemination by DC (debt collectors). Decisive action is needed against illegal online loans by monitoring applications that do not have OJK licenses and blocking them.